EFFECT OF OINTMENT FROM COMBINED Centella asiatica (L.) Urban AND Coleus amboinicus EXTRACTS ON SKIN WOUND TISSUE REPAIR IN DIABETIC RATS - ., Tajul Anshor Fathullah Halimy (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: A single Centella asiatica L. Urban (CALU) extract stimulated cellular proliferation in granulation tissue, while a single Coleus amboinicus L.(CAL) extract acted as antiseptic agent. Diabetic wound closure is sensitivelydifficult to be done because proliferation is likely inhibited by antisepticalteration resulted as infectious wound. Both extracts may give synergy incombination into ointment. Objective: to investigate the effect of combinedextractsointmentonangiogenesis,inflammatorycellsandmicroscopicwounddiameter.Methods:posttestonlygroupdesignwasexperimentallyconducted,sixtyratswererandomly divided into 5 groups; each group was treated withdifferent ointment constituent: single 1,5% CALU extract; single 5% CALextract; both extracts (1,5%CALU+ 5%CAL); placebo and Sanoskin MelladermPlus® (SMP). Diabetic rat’s skin was excised and treated with hydrocarbonbasedointment.Assessmentonangiogenesis,inflammatorycellsandwounddiameterwereobservedhistopathologicallyonday3,7and14aftertreatment.Thedata were analyzed by one-way ANOVA and LSD. Results: combinedextractsointmenteffectwassignificantlydifferent(p<0,05)comparedtoeithersingleCALU, single CAL, placebo or SMP® in term of angiogenesis andinflammatory cells, but not significantly different (p>0,05) compared to SMP®in term of wound diameter reduction. Conclusion: Combined-extractsointment is better than either single extract, placebo or SMP® in improvingangiogenesis and reducing number of inflammatory cells, but not better thanSMP® in reducing wound diameter.Keywords: combined-extracts, single extract, angiogenesis, inflammatory cells, wound diameter.1. Medical School, Faculty of Medicine, Universitas Tanjungpura, Pontianak 2. Departement of Pathology Anatomy, Faculty of Medicine, UniversitasTanjungpura, Pontianak 3. Departement of Physiology, Faculty of Medicine, Universitas Tanjungpura,Pontianak